Influence of Knowledge Management and Innovation on Organizational Performance Enhancement - Hamdedi Hamdedi; Yunita sari; Mardiah Kenamon (Penerbit Goodwood, 2025)
Purpose: The purpose of this study is to analyze the effect of knowledge management on organizational performance with innovation as a mediating variable. This research aims to understand how effectively managing knowledge can foster innovation and ultimately enhance performance within healthcare organizations. Research Methodology: This study employs a quantitative approach, with data collected from 100 employees at the Tanjung Agung Health Center. The sample was selected using the Slovin formula to ensure representativeness. Data were gathered through structured questionnaires and analyzed using SPSS software to test the relationships between knowledge management, innovation, and organizational performance. Results: The results show that knowledge management significantly and positively affects both innovation and organizational performance. Furthermore, innovation functions as a mediating variable, meaning that better knowledge management leads to increased innovation, which subsequently improves organizational performance. These findings are particularly evident among employees at Tanjung Agung Health Center, suggesting the critical role of internal knowledge systems in driving institutional success. Conclusion: The study concludes that effective knowledge management is essential in fostering innovation, which plays a key role in enhancing organizational performance. Promoting a culture of knowledge sharing and learning can yield long-term benefits for institutional development. Limitation: The research was limited to a single health center and focused only on two variables, which restricts the generalizability of the findings across different settings or sectors. Contribution: This study provides valuable insights into how innovation strengthens the link between knowledge management and performance, offering a strategic direction for organizational improvement, especially in healthcare settings.